2019
DOI: 10.1039/c8ra08494g
|View full text |Cite
|
Sign up to set email alerts
|

Crystal phase content-dependent functionality of dual phase SnO2–WO3nanocomposite filmsviacosputtering crystal growth

Abstract: In this study, crystalline SnO2–WO3nanocomposite thin films were grown through radio-frequency cosputtering of metallic Sn and ceramic WO3targets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…Moreover, the gas-sensing responses of ZnO–WO 3 composite nanorods annealed at 400 °C ranged from 2.1 to 16.2 (blue curve in Figure 6a), which demonstrated the highest response among the samples at the tested temperatures. Significantly, the nanorod sensors herein exhibited the maximum gas-sensing responses to ethanol at 300 °C, suggesting that a resultant equilibrium between surface reaction with ethanol vapor molecules and the diffusion of ethanol vapor molecules to the nanorods’ surfaces occurred at 300 °C [9]. Figure 6b–d show the dynamic response curves of ZnO nanorods, ZnO–WO 3 nanorods, and ZnO–WO 3 nanorods annealed at 400 °C, respectively, exposed to 25–500 ppm ethanol vapor at the operating temperature of 300 °C.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the gas-sensing responses of ZnO–WO 3 composite nanorods annealed at 400 °C ranged from 2.1 to 16.2 (blue curve in Figure 6a), which demonstrated the highest response among the samples at the tested temperatures. Significantly, the nanorod sensors herein exhibited the maximum gas-sensing responses to ethanol at 300 °C, suggesting that a resultant equilibrium between surface reaction with ethanol vapor molecules and the diffusion of ethanol vapor molecules to the nanorods’ surfaces occurred at 300 °C [9]. Figure 6b–d show the dynamic response curves of ZnO nanorods, ZnO–WO 3 nanorods, and ZnO–WO 3 nanorods annealed at 400 °C, respectively, exposed to 25–500 ppm ethanol vapor at the operating temperature of 300 °C.…”
Section: Resultsmentioning
confidence: 99%
“…The local phase transformation of the ZnO/WO 3 after thermal annealing at 400 °C for the ZnO–WO 3 composite nanorod system in this study created a higher number of the potential barriers in the composite system as exhibited in Figure 7b. An increased potential barrier number in the composite systems has shown a substantial drop degree of the sensor resistance on exposure to the reducing gases and therefore this resulted in an enhanced gas-sensing response [3,9]. The cross-sectional potential barrier height variation alone the guided arrow red line in Figure 7b demonstrated that a more complex potential barrier height variation before and after introducing the ethanol vapor will be expected for the ZnO–WO 3 composite nanorods with an annealing procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tungsten trioxide (WO 3 ) is an n-type wide bandgap semiconductor with various functionalities [1,2,3,4]. Among numerous applications, WO 3 with various morphologies has received extensive attention as a forward-looking gas-sensing material due to its high sensitivity and stability toward target gases [1,5].…”
Section: Introductionmentioning
confidence: 99%
“…It has been used to detect methanol, ethanol, and ethylene glycol gases with desirable sensing performance [14,15,16]. Although improvement in the gas-sensing performance of SnO 2 nanoparticle-decorated monoclinic WO 3 nanosheets and tetragonal SnO 2 -monoclinic WO 3 composite films has been reported [4,6], gas-sensing properties of hexagonally structured WO 3 nanorods coupled with thin coverage layers of SnO 2 have not yet been proposed. This might hinder the potential applications of hexagonally structured WO 3 -based composite nanorods in gas sensor devices.…”
Section: Introductionmentioning
confidence: 99%